1993
DOI: 10.1104/pp.101.3.1089
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning of Abscisic Acid-Responsive mRNAs Expressed during the Induction of Freezing Tolerance in Bromegrass (Bromus inermis Leyss) Suspension Culture

Abstract: Abscisic acid (ABA) increases the freezing tolerance of bromegrass (Bromus inermis Leyss) cell-suspension cultures at 23'C and elicits many metabolic changes similar to those observed during cold acclimation. lnduction and maintenance of freezing tolerance by ABA is accompanied by the expression of novel polypeptides and translatable RNAs. l h e objective of this study was to isolate and characterize ABA-responsive cDNAs associated with ABAinduced freezing tolerance in bromegrass cell cultures. Among the 16 AB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
37
0
2

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 32 publications
1
37
0
2
Order By: Relevance
“…Therefore, the accumulation of Glc or Sue synthesized from the phosphorylated form of Glc might function as a cryoprotectant in plants exhibiting cold hardiness. In agreement with our results, the up-regulation of aldose reductase and phosphoglucomutase in bromegrass (Lee and Chen, 1993) and Sue synthase in wheat (Crespi et al, 1991) indicates that there is a requirement for genes involved in sugar metabolism during cold acclimation. Whether these changes are biologically significant for the acclimation process or are simply a consequence of adaptation remains to be determined.…”
Section: Dlscusslonsupporting
confidence: 92%
“…Therefore, the accumulation of Glc or Sue synthesized from the phosphorylated form of Glc might function as a cryoprotectant in plants exhibiting cold hardiness. In agreement with our results, the up-regulation of aldose reductase and phosphoglucomutase in bromegrass (Lee and Chen, 1993) and Sue synthase in wheat (Crespi et al, 1991) indicates that there is a requirement for genes involved in sugar metabolism during cold acclimation. Whether these changes are biologically significant for the acclimation process or are simply a consequence of adaptation remains to be determined.…”
Section: Dlscusslonsupporting
confidence: 92%
“…These observations are consistent with the report of Tanino et al (1990), who demonstrated using the same cell culture that (±)-ABA treatment increased Sue uptake. Also, studies using the same culture have shown that (±)-ABA treatment results in the increased expression of genes associated with sugar metabolism (Lee and Chen, 1993). Sue also enhances the freezing tolerance of (±)-ABA-treated bromegrass suspension cultures (Reaney, 1989;Ishikawa et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Although considerable effort has been directed at understanding the structure and function of these proteins in herbaceous plant species (Volger and Heber, 1975; Guy and Haskell, 1989;Hincha and Schmitt, 1992;Houde et al, 1992;Lin and Thomashow, 1992a;Lee and Chen, 1993), reports concerning deciduous fruit trees and woody plants, in general, are limited. Determining whether or not seasonal changes in protein turnover are specifically associated with cold acclimation is difficult because of the fact that overwintering deciduous perennials also enter into endodormancy during the same time as they develop cold hardiness.…”
mentioning
confidence: 99%